La diversidad en el aula, el gran desafío en la actualidad. ¿Están el y la docente preparados para enfrentarlo? - Érika Vásquez-Salazar (Revista Electrónica Educare)
Nowadays, Costa Rican classrooms have become multicultural spaces, characterized by the presence of children from diverse populations, especially because of phenomena such as migrations, but also due to social and economical factors. As a result, diversity within the classroom represents a big challenge for teacher, who are required to educate students with truly dissimilar characteristics while offer them an education in accordance with their specific individual needs. Teaching in the multicultural classroom is a challenge that involves a change of attitude to the “others”. This can only be achieved through the recognition of students as unique and different human beings, people who have a view of the world built through specific life experiences; experiences that have to be taken into account when teaching because this is the basis to succeed or fail as educators. Consequently, it is important to know different approaches that discuss diversity and multiculturalism at the present time, giving us light to find the correct path in order to face this complex reality.